Inflation Targeting vs. Average Inflation Targeting in the New Keynesian Small Open Economy Model - Matloch, Mateusz; Máslo, Lukáš Augustin, 1985-; Potužák, Pavel; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2025)
This thesis investigates the comparative performance of inflation targeting and average inflation targeting monetary policies. In the last decade, low inflation numbers and low interest rates were present. As a reaction, Fed decided to shift the monetary policy paradigm by switching from inflation targeting to average inflation targeting regime. Using the New Keynesian small open economy DSGE model, which is calibrated to fit the Czech economy specification, impulse response functions are generated for the presence of technology shock, world output shock, interest rate shock, world inflation shock, domestic inflation shock, and foreign inflation shock. Since CNB uses flexible inflation targeting and Fed opted to choose flexible average inflation targeting, those regimes are compared. The FAIT regime has three alternatives with different averaging horizons: 4 periods, 8 periods, and 12 periods. This thesis shows that FAIT is a considerable option for monetary policy authorities. Output and consumption behave quite similarly, while the biggest divergence between regimes is in price level and interest rate. FAIT regimes also show a higher degree of fluctuation while converging back to the steady state values.
Vedoucí práce: Lukáš Augustin Máslo
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: ekonomie [obor dipl. práce]; diplomové práce; master's theses